Monitoring of the deuterated and nondeuterated forms of levodopa and five metabolites in plasma and urine by LC–MS/MS. (21st February 2019) - van de Merbel, Nico C; Bronsema, Kees J; Gorman, Steven H; Bakhtiar, Ray
To compare pharmacokinetics, metabolism and excretion of levodopa and a triply deuterated form, which is being developed as an improved treatment for Parkinson's disease, methods were needed for quantification of the deuterated and nondeuterated forms of levodopa and five metabolites in human plasma and urine.Results: The natural heavy isotopes in the nondeuterated compounds caused an absolute contribution of up to 100% in the response of the deuterated compounds. Similarly, heavy isotopes in the deuterated analytes contributed to the response of the internal standards, but this did not affect the reliability of the results.Conclusion: Deuterated and nondeuterated analytes can be quantified together by LC–MS/MS, but overestimation of the concentrations of the deuterated molecules may be unavoidable and a careful interpretation of the concentration data is essential.